Meningkatan Kemampuan Membaca dengan Menggunakan Metode Multisensori VAKT Pada Siswa Sekolah Dasar - Sela Armita Sela; Yulida Angraini Yulida; Hasmi Suyuthi Hasmi; Sakroni Sakroni (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Reading ability is a child's ability to recognize letters and words, then connect them with sounds, and understand the meaning of the writing that is read starting with the ability to listen to letters correctly and precisely. This pkm focuses on the fourth grade students of SDN 75 Bengkulu Tengah as the main object. Instruments used in the form of observation, and documentation. The results of the analysis can be obtained that the reading ability of fourth grade students at SD Negeri 75 Central Bengkulu is still very low. The influencing factors are internal and external factors. Our efforts to improve reading skills at SD Negeri 75 Bengkulu Tengah are providing motivation to learn, practicing reading, repeating lessons that have been given and holding reading learning activities outside of school hours.